1982
DOI: 10.1002/ajpa.1330580308
|View full text |Cite
|
Sign up to set email alerts
|

A new measure of growth efficiency: Skull base height

Abstract: Skull base height increases significantly with better nutrition and health conditions, as seen in comparing 163 nineteenth to twentieth century dissecting-room skeletons (Terry Collection) with 237 modern American middle-class adults (forensic and willed skeletons). The increase parallels the change in pelvic inlet depth index, known to respond sensitively to nutrition, and in stature, and is over six times greater than the general skull size change. Skull base height (porion-basion) is easy to measure with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
5
47
0
1
Order By: Relevance
“…This has a large number of bony elements and each can be affected by harmful environmental factors (Gawlikowska et al 2007a,b andGawlikowska et al 2010). In addition, it may signify insufficient nutrition during growth acting as a stress factor in accordance with Angel's (1982) observation that nutrition and health conditions influence skull-base development. In this regard, he reported that high skull-base fluctuating asymmetry levels are a sensitive measure of nutritional and disease-related stress during growth (Angel 1982).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This has a large number of bony elements and each can be affected by harmful environmental factors (Gawlikowska et al 2007a,b andGawlikowska et al 2010). In addition, it may signify insufficient nutrition during growth acting as a stress factor in accordance with Angel's (1982) observation that nutrition and health conditions influence skull-base development. In this regard, he reported that high skull-base fluctuating asymmetry levels are a sensitive measure of nutritional and disease-related stress during growth (Angel 1982).…”
Section: Discussionsupporting
confidence: 55%
“…In addition, it may signify insufficient nutrition during growth acting as a stress factor in accordance with Angel's (1982) observation that nutrition and health conditions influence skull-base development. In this regard, he reported that high skull-base fluctuating asymmetry levels are a sensitive measure of nutritional and disease-related stress during growth (Angel 1982). The FA index value was medium in medium-sized measurements but higher for longer and very short measurements.…”
Section: Discussionsupporting
confidence: 55%
“…During the last century, nutritional quality has increased and physical activity has decreased, allowing the body more time for growth. One example of how this may have affected skull morphology may be seen in Angel's (1982) suggestion that cranial base height has increased since this region is less flattened in children by the weight of the brain. Some genetic factors may also be in play, however, in that the dramatic reduction in infant mortality over the last 150 years likely is relaxing selection, allowing for greater variability to exist in the gene pool (Jantz, 2001).…”
Section: Resultsmentioning
confidence: 97%
“…Research carried out in the past (Neumann, 1942;Angel & Olney, 1981;Angel, 1982) proved that the height of the skull base is a sensitive and useful measure of developmental stress related mainly to nutritional deficiencies and child disease incidence. Until early childhood, the skull base remains a chondral structure.…”
Section: Skeletal Indications Of Early Developmental Stressmentioning
confidence: 99%